Gestión del régimen disciplinario y su incidencia en el ausentismo laboral en la municipalidad provincial de Chepén: 2019 - Castillo Castañeda, Analy Jennifer (2020)
This thesis had as a general objective, to establish how the Management of the disciplinary regime affects Work Absenteeism in the Provincial Municipality of Chepén: 2019; the problem being: How does the management of the disciplinary regime affect Work Absenteeism in the Provincial Municipality of Chepén: 2019 ?, whose hypothesis establishes that the Management of the disciplinary regime affects in the reverse and significant way the Work Absenteeism in the Provincial Municipality of Chepén : 2019. A non-experimental correlational transectional investigation was developed; the population consisted of 40 workers and eight supervisors, to whom a survey was applied, whose instrument is the questionnaire. The main results are that the Labor Regime Management qualifies at a medium level, since there are inconsistencies regarding the control of faults and penalties, and the Labor Absenteeism qualifies at a high level, since it has been observed that the workers are absent more by factors Personal and organizational. It was concluded that the Disciplinary Regime has an inverse and significant impact on the Labor Absenteeism of the Provincial Municipality of Chepén, since the Pearson Correlation Coefficient is -0.71 for workers and -0.801 for supervisors.